(untitled) (Eurasian Journal of Ecology, 2024)
The article presents the results of critical review of available herbarium specimens of Tulipa borszczowii Regel (Liliaceae) - a rare species listed in the List of Rare and Threatened Plant Species (2006); Red Books: Kazakh SSR (1981), South Kazakhstan (Turkestan) region (2002); Republic of Kazakhstan (2014), Kyzylorda region (2014). The aim of the study was to investigate its current distribution and ecological habitat to identify potential growing sites within the Republic. Specimens of the studied species stored in such major Herbaria as: AA, TASH, MW, LE were reviewed. A total of 147 herbarium specimens were viewed during the study. Also, in the process of work was carried out screening of domestic and foreign sources (including electronic databases) containing information on the places of Tulipa borszczowii growth. As a result of the research: the morphological description of the species was supplemented with detailing the range of color gamma of perianth lobes; the northern boundaries of the Kazakh part of the Tulipa borszczowii area were specified, which are simultaneously the northern limits of distribution of the species as a whole and the list of floristic areas of Kazakhstan in which it is fixed was expanded; a map-scheme of the species locations within the Republic was drawn up; The tasks for further research are formulated, in particular, the need for biometric studies and clarification of both the northwestern and northeastern limits of Tulipa borszczowii growth. Key words: rare species, the red book, Tulipa borszczowii, range, herbarium specimen, mapping.